Studies in gynaecology in zad al-musafir wa qut al- hadir of Abu Jaafar Ibn al-Jazzar - Nordin, Nor Hidayati Diyana; Othman, Raihan (IIUM Press, 2011)
The main focus of this chapter is to present the work of Ibn AI-Jazzar in his sixth book of Zad al-Musafir wa Qut al-Hadir which focuses on gynaecology. The significance of the research is to show that with high commitment, one can excel in any area that he explores. The methodology adopted in completing this research is mainly based on information seeking. Books, journals and the information technology (internet) were made used in achieving the goal to educate the readers on this subject. In 1993, Prof Dr. Gerrit Bos from Germany had published an article entitled Ibn AI-Jazzar on Women's Diseases in the 37th volume of Medical History and thus, this article has provided me the most extensive information in conducting this research